Stochastic resonance in the human vestibular system – Noise-induced facilitation of vestibulospinal reflexes - Wuehr, M.; Boerner, J.C.; Pradhan, C.; Decker, J.; Jahn, K.; Brandt, T.; Schniepp, R. (Brain stimulation, 2018)
There is strong evidence that the presence of noise can enhance information processing in sensory systems via stochastic resonance (SR). To examine the presence of SR in human vestibulospinal reflex function. Healthy subjects were stimulated with 1 Hz sinusoidal GVS of varying amplitudes (0–1.9 mA). Coherence between GVS input and stimulation-induced motion responses was determined and psychometric function fits were subsequently used to determine individual vestibulospinal reflex thresholds. This procedure was repeated with additional application of imperceptible white noise GVS (nGVS). nGVS significantly facilitated the detectability of weak subthreshold vestibular inputs (p < 0.001) and thereby effectively lowered the vestibulospinal threshold in 90% of participants (p < 0.001, mean reduction: 17.5 ± 14.6%). This finding provides evidence for the presence of SR-dynamics in the human vestibular system and gives a functional explanation for previously observed ameliorating effects of low-intensity vestibular noise stimulation on balance control in healthy subjects and patients with vestibular hypofunction. •A new test for human vestibulospinal reflex thresholds is presented.•Evidence for stochastic resonance in the human vestibular system is provided.•Vestibular noise stimulation enables the processing of subthreshold vestibular inputs.•This effect lowers vestibulospinal reflex thresholds by in average 18%.